Proteomic analysis of the chemosensitizing effect of curcumin on CRC cells treated with 5-FU - Yang, Jingbo; He, Chengyan; Liu, Ning (Frontiers in Medicine, 2022)
Background 5-Fluorouracil (5-FU) is one of the most common chemotherapy drugs used to treat colorectal cancer (CRC), which often develops resistance in more than 15% of patients. Curcumin, an active component of Curcuma longa, has been reported to show antitumor activity in CRC and, furthermore, enhance the effect of chemotherapy against colorectal cancer cells. However, the molecular mechanisms underlying the sensitizing effect of curcumin on 5-FU have not been largely elucidated. In this study, we aimed to systematically investigate the role of curcumin as a chemosensitizer for the treatment of CRC, along with the key events responsible for its pharmaceutical effect, which may lead to better clinical outcomes. Methods A high-resolution 2DE-based proteomics approach was used to characterize global protein expression patterns in CRC cells treated with 5-FU both in combination with curcumin or without. The differentially expressed proteins were obtained from the 2DE analysis and subsequently identified by MALDI-TOF MS or nano-ESI-MS/MS, some of which were validated by the Western blot. Intracellular reactive oxygen species (ROS) were measured to assess the change in the redox environment resulting from the drug treatment. Results A series of proteins with altered abundances were detected and identified by MALDI-TOF or nano-MS/MS. From a total of 512 isolated proteins, 22 proteins were found to be upregulated and 6 proteins were downregulated. Intracellular ROS was significantly elevated after curcumin treatment. Furthermore, mass spectrometry data revealed that some of the proteins appeared to have more oxidized forms upon curcumin treatment, suggesting a direct role for ROS in the chemosensitizing effect of curcumin. Conclusion The effect of curcumin in enhancing chemosensitivity to 5-FU is a complex phenomenon made up of several mechanisms, including enhancement of the intracellular level of ROS. Our findings presented here could provide clues for a further study aimed at elucidating the mechanisms underlying the chemosensitizing effect of curcumin.